2019
DOI: 10.18358/np-29-2-i3043
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of the Series of Blood Serum Markers Without Its Preliminary Fractionation Using the Special Features of Tripsine Interaction With Alpha-2-Macroglobulin Using Maldi-MS

Abstract: Предложен способ модификации мишени для МАLDI-МS-анализа, позволяющий селективно выделять аналиты из биологических образцов непосредственно на поверхности мишени, как альтернатива классическим методам. Для модификации мишени суспензию металл-аффинного сорбента на основе оксида железа(III) в 50% водно-метанольном растворе электрораспыляли в бескапельном режиме c динамическим делением потока жидкости при атмосферном давлении в нормальных условиях. МАLDI-мишень выступала в качестве противоэлектрода. На МАLDI-мише… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…Since the proteolytic activity of trypsin in complex with A2M is limited, and it loses the ability to hydrolyze major serum proteins (for example, albumin) due to their large sizes (well above 20 kDa), such A2M-trypsin complexes may be useful as a research tool for identifying minor, small serum proteins. It has been shown earlier that serum amyloid A (SAA) fragments can be detected in mass spectra after serum treatment with trypsin for two hours [8,20]. Thus, it was observed in our experiments that some other ions, that differ from SAA, appear in the mass spectrum with longer incubation of serum with trypsin (marked by asterisk in Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Since the proteolytic activity of trypsin in complex with A2M is limited, and it loses the ability to hydrolyze major serum proteins (for example, albumin) due to their large sizes (well above 20 kDa), such A2M-trypsin complexes may be useful as a research tool for identifying minor, small serum proteins. It has been shown earlier that serum amyloid A (SAA) fragments can be detected in mass spectra after serum treatment with trypsin for two hours [8,20]. Thus, it was observed in our experiments that some other ions, that differ from SAA, appear in the mass spectrum with longer incubation of serum with trypsin (marked by asterisk in Fig.…”
Section: Resultssupporting
confidence: 67%
“…In our previous study [20], the possibility of A2M concentration assessment, directly in human blood serum, was demonstrated. Briefly, it was shown that: after addition of trypsin to serum and a few minutes of incubation, an intense, singly-protonated quasimolecular ion ( m / z = 1259 .…”
Section: Resultsmentioning
confidence: 99%
“…690-728), as expected; this region is involved in trypsin binding and inactivation by A2M in blood serum. It was also shown that the amount of peptide detected is equal to the amount of trypsin bound with A2M [20].…”
Section: Results and Discussion 31 Basic Principlesmentioning
confidence: 94%
“…In our previous study [20], the possibility of A2M concentration assessment, directly in human blood serum, was demonstrated. Briefly, it was shown that: after addition of trypsin to serum and a few minutes of incubation, an intense, singlyprotonated quasimolecular ion ( ⁄ = 1259.57) is registered in the MALDI mass spectrum.…”
Section: Results and Discussion 31 Basic Principlesmentioning
confidence: 99%
See 1 more Smart Citation